PERSIAPAN TEKNIS PEMBANGUNAN TRANSPORTASI CEPAT MASAL DI JAKARTA - ibrahim, irwan (Jurnal Sains dan Teknologi Indonesia, 2010)
Jakarta as a capital city with more than ten million people is facing transportation problems which are already at a critical stage. Such problem can not be solved with conventional approach any more. Alternative solution by deploying Trans Jakarta bus fleet can not bring significant results. Classical constraints such as bad coordination, sectoral interest of related parties still become the main hurdle. Whether we like it or not, mass rapid transport (MRT) system has to be developed in Jakarta. Based on experiences of some cities abroad. MRT solution is absolutely the right choice. This paper presented typical insight of MRT abroad, followed with technical preparation of Jakarta MRT project starting from planning, implementation, up to key factors that should be well considered in order to avoid the failure of project execution.